Video-evoked neuromarkers of visual function in age-related macular degeneration - Renton, Angela I.; Klein, David J.; Livezey, Jesse A.; Nemrodov, Dan; Wolfer, Stephanie; Hanina, Adam; Van De Ville, Dimitri (Frontiers in Human Neuroscience, 2025)
Neural markers of visual function in age-related macular degeneration (AMD) allow clinicians and researchers to directly evaluate the functional changes in visual processing which occur as a result of the progressive loss of afferent input from the macula. Unfortunately, few protocols exist that elicit such neural markers, and most of these are poorly adapted to AMD. Here, we propose a novel method of embedding frequency tags into full color and motion videos by periodically manipulating the contrast of visual information of different spatial frequencies at different temporal frequencies. These videos elicit steady-state visual evoked potentials (SSVEPS) in viewers which, when measured using electrophysiological neuroimaging methods, independently represent the responses of populations of neurons tuned to the tagged spatial frequencies. We used electroencephalography (EEG) to record the SSVEPs of 15 AMD patients and 16 age-matched healthy controls watching a 6-min series of natural scene videos filtered with this spatial frequency tagging method. Compared with healthy controls, AMD patients showed a lower SSVEP to high spatial frequency information, and a stronger response to the low spatial frequency information in the video set. The ratio of the SSVEP to lower relative to higher spatial frequency information was strongly predictive of both visual acuity and contrast sensitivity, and the topographic distributions of these responses suggested retinotopic reorganization of the neural response to spatial frequency information.